Strategi Humas dalam Membangun Citra, Kepercayaan, dan Reputasi Sekolah Islam: Studi di SD Muhammadiyah 1 Samarinda - Rosmayani, Meirina; Julaihah, Siti; Wijaya, Ida Suryani (Itqan: Jurnal Ilmu-ilmu Kependidikan, 2025)
This article discusses the strategic role of public relations in building a positive image of Islamic-based elementary schools, using a case study of SD Muhammadiyah 1 Samarinda. The study aims to identify the communication strategies implemented by the school's public relations team to strengthen public trust and examine their impact on institutional reputation and competitiveness. A qualitative approach with a descriptive method was employed to collect data through observation, interviews, and documentation. The findings reveal that a positive school image is shaped through consistent educational services, open communication, and active participation in community-based activities. Public relations serves as a vital bridge between the school and the public, utilizing digital media, particularly social media, as an effective communication tool. A strong institutional image has been shown to enhance parental trust, community loyalty, and interest in student enrollment. These findings highlight the importance of integrating digital communication strategies into the management of public relations at the elementary education level. Theoretically, this article contributes to the literature on institutional communication management in Islamic educational settings and proposes a value-based and adaptive model of public relations practice in the digital era.